Improving K-12 STEM education outcomes through technological integration - Urban, Michael J., 1977-; Falvo, David A., 1960-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book focuses on current research surrounding the effectiveness, performance, and benefits of incorporating various technological tools within science, technology, engineering, and mathematics classrooms, focusing on evidence-based approaches and current educational innovations"--Provided by publisher.
A qualitative study of teachers' understanding of sustainability: education for sustainable development (ESD), dimensions of sustainability, environmental protection / Hsiaowei Cristina Chang, Resa Marie Kelly, Ellen P. Metzger -- Coupling geospatial and computer modeling technologies to engage high school students in learning urban ecology / Dennis J. DeBay [and 6 others] -- Using technology to rethink the intersection of statistics education and social justice / Lisa L. Poling, Nirmala Naresh, Tracy J. Goodson-Espy -- Using authentic earth data in the K-12 classroom / Meghan E. Marrero, Amanda M. Gunning, Karen Woodruff -- Exploring physics and technology: a study in teaching kinematics to student-athletes / Loraine Snead, Yushaneen Simms -- Computer programming in elementary and middle school: connections across content / Danielle Boyd Harlow [and 6 others] -- Technology's role in supporting elementary preservice teachers as they teach: an urban STEM afterschool enrichment program / Anne Pfitzner Gatling -- Technology-assisted formative assessment / Karen E. Irving -- Using reason racer to support argumentation in middle school science instruction / Marilyn Ault [and 5 others].
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 11/18/2015).
Keywords: Science -- Study and teaching -- Technological innovations; Educational technology; Distance learning; Gaming technologies; Hand-held devices; Internet technologies; Social media; Software applications; Electronic books